DIFFICULTIES ENCOUNTERED BY ENGLISH TEACHERS IN TEACHING VOCABULARIES - Sari, Suci Noer Wulan; Wardani, Niken Anastasia Kusuma (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2019)
This study aims at identifying some difficulties encountered by English teachers in teaching vocabulary and finding out the solutions. The design used was qualitative descriptive using a semi-structured interview as the instrument. The study showed that common difficulties encountered in teaching vocabulary are students? and teachers? limited knowledge of the words, techniques, time constraint, and word selection. To overcome those difficulties, teachers may employ some techniques in teaching vocabulary such as using translation in L1, picture, real objects, gestures, guessing from the context, drilling, repetition, and using dictionary. Thus, it can be concluded that difficulties in teaching vocabulary lead English teachers to some ways they can take to overcome them. For future studies, it is suggested to employ observation to see the practice of vocabulary teaching and find out what the actual difficulties are encountered. Moreover, interview to students might be carried out to see their own difficulties in learning vocabulary.Keywords: English teaching, vocabulary, difficulties, techniques